Smart markets for water resources : a manual for implementation - Raffensperger, John F.; Milke, Mark W. (Springer, 2017)
Why is trade in wholesale water so rare, when markets can actively trade bread, tractors, and electricity? This book shows that water markets fail because of high transaction costs, resulting in inefficient allocations and unpredictable environmental effects. To overcome these obstacles, this book proposes a trading mechanism called a smart market. A smart market is an auction cleared with optimization. A smart market can reduce the transaction costs of water trading, while improving the environmental outcomes. The authors show why a smart market for water is needed, how it would work, and how to implement it. The smart market described here uses a hydrology simulation of the water resource, user bids via the internet, and mathematical optimization, to maximize the economic value of water while meeting all environmental constraints. The book provides the background to understand the smart market for water, and the detail to help the reader start working on its application. The book explores topics such as: Why water should be more expensive near sensitive environmental locations, Ways to set initial allocations of water rights, The role of regulatory oversight, The prerequisites of a water market, and How to counter objections to water markets. The culmination of a decade of investigation, this book combines explanation, examples, and detail to inform policymakers, large water users, environmental organizations, researchers, and a thirsty public.
Keywords: Water resources development.; Water resources development -- Government policy.; Water-supply -- Management.; elektronické knihy; electronic books